First discovery of two polyketide synthase genes for mitorubrinic acid and mitorubrinol yellow pigment biosynthesis and implications in virulence of Penicillium marneffei. - Patrick C Y Woo; Ching-Wan Lam; Emily W T Tam; Chris K F Leung; Samson S Y Wong; Susanna K P Lau; Kwok-Yung Yuen (Public Library of Science (PLoS), 2012)
BACKGROUND:The genome of P. marneffei, the most important thermal dimorphic fungus causing respiratory, skin and systemic mycosis in China and Southeast Asia, possesses 23 polyketide synthase (PKS) genes and 2 polyketide synthase nonribosomal peptide synthase hybrid (PKS-NRPS) genes, which is of high diversity compared to other thermal dimorphic pathogenic fungi. We hypothesized that the yellow pigment in the mold form of P. marneffei could also be synthesized by one or more PKS genes. METHODOLOGY/PRINCIPAL FINDINGS:All 23 PKS and 2 PKS-NRPS genes of P. marneffei were systematically knocked down. A loss of the yellow pigment was observed in the mold form of the pks11 knockdown, pks12 knockdown and pks11pks12 double knockdown mutants. Sequence analysis showed that PKS11 and PKS12 are fungal non-reducing PKSs. Ultra high performance liquid chromatography-photodiode array detector/electrospray ionization-quadruple time of flight-mass spectrometry (MS) and MS/MS analysis of the culture filtrates of wild type P. marneffei and the pks11 knockdown, pks12 knockdown and pks11pks12 double knockdown mutants showed that the yellow pigment is composed of mitorubrinic acid and mitorubrinol. The survival of mice challenged with the pks11 knockdown, pks12 knockdown and pks11pks12 double knockdown mutants was significantly better than those challenged with wild type P. marneffei (P<0.05). There was also statistically significant decrease in survival of pks11 knockdown, pks12 knockdown and pks11pks12 double knockdown mutants compared to wild type P. marneffei in both J774 and THP1 macrophages (P<0.05). CONCLUSIONS/SIGNIFICANCE:The yellow pigment of the mold form of P. marneffei is composed of mitorubrinol and mitorubrinic acid. This represents the first discovery of PKS genes responsible for mitorubrinol and mitorubrinic acid biosynthesis. pks12 and pks11 are probably responsible for sequential use in the biosynthesis of mitorubrinol and mitorubrinic acid. Mitorubrinol and mitorubrinic acid are virulence factors of P. marneffei by improving its intracellular survival in macrophages.